Ensuring Antibiotic Development, Equitable Availability, and Responsible Use of Effective Antibiotics: Recommendations for Multisectoral Action. (26th September 2018) - Monnier, Annelie A; Schouten, Jeroen; Tebano, Gianpiero; Zanichelli, Veronica; Huttner, Benedikt D; Pulcini, Céline; Årdal, Christine; Harbarth, Stephan; Hulscher, Marlies E; Gyssens, Inge C
Abstract : This viewpoint presents recommendations for lifting the barriers to antibiotic development, equitable availability of effective (existing and new) antibiotics, and responsible antibiotic use. These recommendations should guide future, multisectoral policy action. Abstract: Antibiotic resistance is a growing threat to global public health. The World Health Organization's Global Action Plan on Antimicrobial Resistance recommends engaging multisectoral stakeholders to tackle the issue. However, so far, few studies have addressed barriers to antibiotic development, equitable availability, and responsible antibiotic use from the perspective of stakeholders outside healthcare facilities or patient communities: the so-called third-party stakeholders. Third-party stakeholders include, inter alia, governments, regulatory agencies, and professionals working in antibiotic research and development and medical ethics. This viewpoint provides an overview of barriers to antibiotic development, equitable availability of effective antibiotics, and the responsible use of antibiotics. The barriers were identified in an exploratory, qualitative interview study with an illustrative sample of 12 third-party stakeholders. Recommendations to lift these barriers are presented, together with examples of recently-made progress. The recommendations should guide future antibiotic policies and multisectoral policy action.